Medicinal Plants Used for Traditional Medicine in Ethnobotanical Studies in Nagari Padang Laweh, Sijunjung Regency - Gina Julia; Nursyahra Nursyahra; Zikra Zikra (UNIVERSITAS NEGERI PADANG, 2023)
This studi aims to determine medicinal plants used for tradisional medicine in ethnobotanical studies in Nagari Padang Laweh, Sijunjung Regency. This information can be obtained by the community as a reference for traditional medicine that has been passed down from generation to generation. The method used in this research is descriptive survey method. Medicinal plant species were identified in the field and continued at the Botanical Laboratory of PGRI University, West Sumatra. In this study obtained 81 species of medicinal plants. Not all medicinal plants used in Nagari Padang Laweh are also used as medicine elsewhere, so this knowledge can be used as an asset and needs to be preserved.